Properties, materials and durability of rolled compacted concrete for pavements - Ćurčić Gordana Topličić; Dušan Grdić; Nenad Ristić; Zoran Grdić (Zaštita Materijala)
Roller-Compacted Concrete (RCC) consists of an engineered mixture of dense-graded aggregates, cement and water. This zero slump concrete mixture, when placed with an asphalt paver and compacted to high density, provides a high-strength, durable pavement structure. RCC uses no forms, requires no conventional finishing, and needs no dowels or reinforcing steel, making it an economical choice. The low water-cement ratio (usually ranging from 0.30 to 0.40) provides for very high strengths. Common design unconfined compressive strengths for pavements are in the range of 35 to 55 MPa. With the low water-cement ratio there is less paste in the concrete matrix, so there is no bleed water and less shrinkage than in conventional PCC. In the past 30 years it has gained acceptance as a strong and durable pavement material that can withstand heavy loads and severe climates with little required maintenance.